Early onset children's Gitelman syndrome with severe hypokalaemia: a case report - Hanjiang Chen; Rong Ma; Hongzhe Du; Jin Liu; Li Jin (BMC, 2020)
Abstract Background Hypokalaemia is a common condition among paediatric patients, but severe hypokalaemia is rare and can be life-threatening if not treated properly. The causes of hypokalaemia are complex. Finding the root cause is the key. Case presentation This article reports on a 2-year-old boy with severe hypokalaemia who was diagnosed with pneumonia. The child's lab findings were low blood potassium minimum level of 1.7 mmol/L, hypomagnesemia, and metabolic alkalosis. However, he was without the common features of hypokalaemia, such as respiratory paralysis, severe arrhythmia, weakness and decreased blood pressure. After recovering from pneumonia, his potassium levels did not return to normal. This outcome was suspected to be due to chronic renal loss of potassium. After undergoing second-generation gene sequencing tests, it was discovered he carried the SLC12A3 gene mutation with an Asp486Asn mutation site, which he had inherited from his mother. The final diagnosis was made, confirming the child suffered from Gitelman syndrome. Conclusions Genetic predisposition is an important cause of hypokalaemia in children. Children with unexplained persistent hypokalaemia should be examined for the possibility of Gitelman syndrome, which should be distinguished from Bartter syndrome. Genetic testing is the gold standard.